Modern Trends, Examples and Methods for Assessing Physical Activity of City Residents - D. A. Andreev; N. N. Kamynina (Здоровье мегаполиса, 2024)
Introduction. A sufficient level of physical activity (PA) is crucial for maintaining population health. There is a wide range of methods and approaches to PA assessment, such as questionnaires that are a convenient tool for assessment of PA levels. Another modern way to assess PA is individual wearable devices, including accelerometers. Data obtained from accelerometers and other tools can contribute to questionnaire results used in PA studies. Purpose. This review was carried out with the aim of considering modern trends, examples and common methods of physical activity assessment of city residents.Materials and methods. Relevant information was collected using PubMed and E-Library databases. Google and Yandex search systems were used to obtain additional data.Results. This paper describes global trends in modern PA studies, presents the examples of Russian and foreign papers on PA of city population, as well as summarizes the main features of PA assessment tools. Notably, PA can be assessed using subjective and objective methods. International and national questionnaires are widely applied as a subjective assessment tool. At the same time, technologies for objective assessment based on digital systems, wearable devices and other approaches to PA monitoring are being developed. Methods for assessing PA can be selected in several stages using decision-making algorithms.Conclusions. Upon the obtained results we assume that modern study design and methods of assessment of PA level among city residents helps to identify factors influencing the formation and maintenance of healthy lifestyle in urban environment.